Assessment of Chemistry Teachers’ Knowledge on Entrepreneurial Chemistry Topics in Senior Secondary Schools - Onwudinjo, Felicity Uju (Journal of Education and Teacher Training Innovation, 2024)
The study investigated the entrepreneurship knowledge of chemistry teachers in Otuocha education zone of Anambra state, towards some topics in senior secondary school chemistry curriculum. Three research questions guided the study. 31 chemistry teachers from Otuocha education zone were involved. Twenty-four item questionnaire generated from five branches of chemistry mainly taught in senior secondary schools were used for data collection. The instrument was validated and its reliability was found to be 0.91 using Cronbach alpha. The data analysed using mean and standard deviation indicated that twelve (12) out of the twenty three topics were found not to be significant on teachers’ knowledge of entrepreneurship in teaching. This is an indication that students are not being cultured with these skills during lesson. This was also confirmed in the analysis of the data collected from how teachers relate the topics to real world / entrepreneurial skill, where sixteen (16) out of twenty three topics were found not to be significant on teachers’ in relating to entrepreneurship in teaching. Out of the fifteen (15) entrepreneurial teaching strategies tested, twelve were found not to be significant on teachers’. Some recommendations were made based on the findings to improve the development of entrepreneurial skills in students.